MANAJEMEN KURIKULUM DALAM MENINGKATKAN MUTU LULUSAN MADRASAH IBTIDAIYAH - Nunik Pramulyani (Latifah Pres, 2019)
Education is an important thing that supports the progress of a country. Because with quality education will produce quality individuals, who are able to compete with other countries and be able to face the flow of globalization. Then we need to support and participate in advancing education. The quality of education will be satisfactory if managed well. To achieve good education there is a need for good management, especially in the curriculum. Curriculum management is a regulatory activity that includes planning, organizing, implementing, and evaluating so that the education program can run well and in accordance with the expected goals. By implementing good curriculum management, these educational institutions will produce quality graduates.